ORTHODONTIC FORCE DIFFERENCE ON ACTIVE COMPONENTS ACTIVATION OF REMOVABLE ORTHODONTIC APPLIANCES (PERBEDAAN BESAR GAYA ORTODONTI PADA AKTIVASI KOMPONEN AKTIF PERANTI ORTODONTI LEPASAN) - Egriphina Novi Mariza; Pricillia Priska Sianita (Journal of Health and Dental Sciences, 2022)
Orthodontic treatment is performed by moving the malposition teeth into a good position in the dental arch with a removable or fixed orthodontic appliance. In this regard, the removable orthodontic appliance has an active component to transmit the orthodontic force that will result in orthodontic tooth movement. The orthodontic force used must be optimal in the sense of being able to produce tooth movement without causing side effects that endanger the periodontal tissue. It is necessary to activate the active components of the appliance, which in orthodontic treatment can be done several times until the desired tooth position is achieved. This study aims to explain the differences in orthodontic force in activating active components of removable orthodontic appliances. The research method was an experimental laboratory. A total of 24 removable orthodontic appliances used in this study were divided into two groups. The first group has a Z spring or single cantilever spring active component, and the other group has a labial bow. Each active component is activated by opening the loop by 1mm, 1.5mm, and 2mm, and in each activation, the magnitude of the force generated is measured using a tension gauge. Data analyzed by Mann Whitney (p<0.05). The result showed different activations carried out in this study resulted in significantly different forces with p=0.029. The force generated in each activation increases as the loop opening increases. Based on that results, it can be concluded that there is a significant difference in the force magnitude generated by the activation of the removable orthodontic appliance active component. DOI : 10.54052/jhds.v1n3.p317-328